1989
DOI: 10.1056/nejm198903093201003
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Relapse or Survival in Patients with Node-Negative Breast Cancer by DNA Flow Cytometry

Abstract: More accurate prediction of the prognosis in women with node-negative breast cancer may improve physicians' ability to identify the patients most likely to benefit from systematic adjuvant therapy. With this in mind, we performed DNA flow-cytometric measurements of ploidy and the fraction of cells in the synthesis phase of the cell cycle (S-phase fraction) on 395 specimens of node-negative breast cancer from our bank of frozen tumors, using the aliquots of pulverized frozen tissue from steroid-receptor assays.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
180
5
4

Year Published

1990
1990
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 520 publications
(207 citation statements)
references
References 25 publications
18
180
5
4
Order By: Relevance
“…In a large study of (Silvestrini et al, 1995). As in our study, SPF has been found to be a significant prognostic factor of distant metastasis in diploid but not in aneuploid tumours (Clark et al, 1989). A similar observation has been made in soft-tissue sarcomas (Huuhtanen et al, 1996).…”
Section: Discussionsupporting
confidence: 91%
“…In a large study of (Silvestrini et al, 1995). As in our study, SPF has been found to be a significant prognostic factor of distant metastasis in diploid but not in aneuploid tumours (Clark et al, 1989). A similar observation has been made in soft-tissue sarcomas (Huuhtanen et al, 1996).…”
Section: Discussionsupporting
confidence: 91%
“…Multiple sample statistical tests were performed by the comparing survival in multiple groups module (24) and the Cox proportional hazards statistical tests in the regression models module (44,45). DNA ploidy and S-phase proportional hazards assumption was verified by graphical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In the 1980s, hundreds of flow cytometry papers demonstrated prognostic significance of DNA ploidy and/or S-phase for many types of solid tumors (16 -22). In particular, many studies showed that S-phase and, in some cases, DNA ploidy could stratify node-negative breast cancer patients into low-and high-risk groups for relapse and death (23)(24)(25), potentially giving oncologists more options in treating this prevalent and deadly disease. Unfortunately, many studies found that S-phase and DNA ploidy were highly correlated.…”
mentioning
confidence: 99%
“…For instance, Lelle et al (1986) described a significant difference in the size of growth fractions -as detected by immunostainingbetween benign and malignant breast lesions. Other authors indicated that breast cancer patients with highly proliferating tumours as assessed by immunostaining (Sahin et al, 1991;Veronese et al, 1993) or S-phase evaluation (Clark et al, 1989;Sigurdsson et al, 1990) have an increased risk of recurrence.…”
mentioning
confidence: 99%